2019
DOI: 10.1002/med.21578
|View full text |Cite
|
Sign up to set email alerts
|

A review of the molecular design and biological activities of RXR agonists

Abstract: An attractive approach to combat disease is to target theregulation of cell function. At the heart of this task are nuclear receptors (NRs); which control functions such as gene transcription. Arguably, the key player in this regulatory machinery is the retinoid X receptor (RXR). This NR associates with a third of the NRs found in humans. Scientists have hypothesized that controlling the activity of RXR is an attractive approach to control cellular functions that modulate diseases such as cancer, diabetes, Alz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 134 publications
0
28
0
2
Order By: Relevance
“…RXR functions as a binding partner for PXR and CAR as well as several other type 2 nuclear receptors. Although RXR is often regarded as a passive partner, RXR may also bind ligands such as 9- cis retinoic acid (de Almeida and Conda-Sheridan 2019 ) and it has been reported that RXR ligands may modulate function of the dimers formed by RXR and the xenobiotic-sensing receptors (Chen et al 2010 ). It has also been reported that retinoids could induce CYP3A4 through RXR/VDR heterodimers and RXR homodimers (Wang et al 2008 ).…”
Section: Mechanisms Of Cyp Inductionmentioning
confidence: 99%
“…RXR functions as a binding partner for PXR and CAR as well as several other type 2 nuclear receptors. Although RXR is often regarded as a passive partner, RXR may also bind ligands such as 9- cis retinoic acid (de Almeida and Conda-Sheridan 2019 ) and it has been reported that RXR ligands may modulate function of the dimers formed by RXR and the xenobiotic-sensing receptors (Chen et al 2010 ). It has also been reported that retinoids could induce CYP3A4 through RXR/VDR heterodimers and RXR homodimers (Wang et al 2008 ).…”
Section: Mechanisms Of Cyp Inductionmentioning
confidence: 99%
“…RARs and RXRs are both found in humans as three different subtypes, α, β, and γ, each of which with several isoforms, that can have different functions and tissues' distribution and so, can activate different genes [4]. RXRs are known as the favoured heterodimerization partner for one-third of the total nuclear receptors, first of all RARs [5]. The ligand-activated transcription factors exert their action by biding to retinoic-acid responsive elements (RAREs) present on retinoid-responsive genes [6].…”
Section: Introductionmentioning
confidence: 99%
“…4-oxo-) derivatives of retinoic acids dominate over the parent compounds. Besides dietary excreted retinoids, pharmaceutical retinoids (tretinoin (atRA), alitretinoin (9cRA), isotretinoin (13cRA), bexarotene, and others; pharmaceutical use: cancer, acne (≥ 0.5 mg isotretinoin/kg/days), eczema treatment [222,284,285]) and cosmetically used retinoids (retinol, retinyl palmitate, retinyl acetate; cosmetic use: body lotion (≤ 0.05% retinol equivalent), hand/face cream or rinse-off products (≤ 0.3% retinol equivalent) [279,286]) can be excreted into wastewaters or washedoff after topical application. The use of retinoic acid in cosmetics is restricted within the EU and Norway [70,286,287], recommendations are provided by the European Medical Agency, with respect to oral use of the retinoid containing medicinal products in pregnancy, and also for those suffering from neuropsychiatric disorders [222].…”
Section: European and Asian Environmental Case Examplesmentioning
confidence: 99%